Tangled crises in Turkana: investigating the spread of Prosopis in Kenya's northern drylands - Derbyshire, Samuel F.; Leakey, Acacia; Lowasa, Lucas (Cambridge University Press, 2023)
Following a severe drought in the late 1970s and early 1980s, the invasive shrub Prosopis, a kind of mesquite native to South America, was introduced by international organizations to locations across Kenya’s drylands, including the Turkana region in the far north. Prosopis, known as etirae in Turkana, was envisaged as a solution to a range of problems, including deforestation, fuelwood shortages and general environmental deterioration. While exacerbated by drought, these problems were perceived to reflect a much more fundamental crisis, with prevalent views at the time envisaging pastoralism as unsustainable, destructive and in need of overhaul – a narrative dating to colonial times that has since been discredited. Since its introduction, etirae has spread relentlessly, invading riparian land, encroaching on cultivation plots and growing to new heights and thicknesses. Investigating its entanglements with Turkana livelihoods and economic relationships is also a process of understanding how it has braided its way through contested processes of social change, and how it has come to be intertwined with conceptions of cascading crisis quite distinct from the narratives that led to its initial introduction. Implications emerge regarding both the complicated biological residues of past development interventions and the totalizing crisis-oriented narratives that shape drylands development in the current era of climate change.